Pengaruh Country Of Origin, Brand Image, Dan Perceived Quality Terhadap Kepuasan Pelanggan Serta Dampaknya Pada Wom (Word Of Mouth) (Survey Pada Pelanggan Handphone Merek Oppo Di Kota Pontianak) - Steven Steven; Novyriantika Novyriantika (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2019)
Country of origin, brand image, perceived quality was good and the good will of course have been an impact on customer satisfaction, if customers are satisfied with the purchased product will certainly recommend to others products bought and will create a wom positive. This study wants to prove the effect of each variable is the country of origin, brand image, perceived quality, and customer satisfaction as an intervening variable on word of mouth on the user’s mobile phone brand OPPO in Pontianak. Based on previous studies and are associated with supporting the theory put forward by the experts using SPSS as statistical data processing devices. This type of research is assosiative research. In this study, researchers used a technique nonprobability sampling because researchers do not know the total number of members of the population studied. While the sampling technique used in this research is accidental sampling. While the sampled population of 100 people, with data analysis techniques using path analysis (Path Analysis). Based on the data processing using path analysis, it is evident that the country of origin, brand image, and perceived quality effect on customer satisfaction and country of origin, brand image, perceived quality and customer satisfaction is also positive and significant effect on word of mouth with customer satisfaction as an intervening variable.